Law and personality disorder: human rights, human risks, and rehabilitation - O'Loughlin, Ailbhe (Clarendon studies in criminology, 2024)
Ailbhe O'Loughlin deconstructs competing images of 'dangerous' offenders with personality disorders and the legal dilemmas they present. She examines gaps in criminological arguments for preventative detention programmes, developing a deeper interpretation of the laws governing personality disordered offenders.